Connections between Immune-Derived Mediators and Sensory Nerves for Itch Sensation - Sumika Toyama (MDPI AG, 2021)
Although histamine is a well-known itch mediator, histamine H1-receptor blockers often lack efficacy in chronic itch. Recent molecular and cellular based studies have shown that non-histaminergic mediators, such as proteases, neuropeptides and cytokines, along with their cognate receptors, are involved in evocation and modulation of itch sensation. Many of these molecules are produced and secreted by immune cells, which act on sensory nerve fibers distributed in the skin to cause itching and sensitization. This understanding of the connections between immune cell-derived mediators and sensory nerve fibers has led to the development of new treatments for itch. This review summarizes current knowledge of immune cell-derived itch mediators and neuronal response mechanisms, and discusses therapeutic agents that target these systems.